FETES: a fast, emergency timeslot allocation, and three-tier energy saving-based task execution strategy for wireless body area network. (2nd March 2023) - Chowdhury, Mahfuzulhoq
Wireless body area network (WBAN) is becoming increasingly popular among researchers and patients due to its real-time healthcare services. Mobile-edge computing (MEC) can play a major role to satisfy the latency requirements of WBAN's healthcare applications. The development of a suitable computation offloading and energy savings scheme is critical for MEC-enabled WBANs due to different priorities of WBAN tasks, QoS, resource availability, and contention delay. To improve the end-to-end latency, this paper proposes a fast data transfer, emergency timeslot, processing node allocation, and energy-saving-based task execution strategy (FETES) considering WBAN user's task priority, multiple tasks, resources, availability, different delays, network connectivity, and processing devices for computation offloading. The FETES scheme supports energy-saving for sensors, hubs, and network access devices. To evaluate the delay, throughput, and energy dissipation performance of the proposed FETES scheme, a comprehensive analytical model is presented. The evaluation results show the efficacy of the proposed FETES scheme.